Perancangan strategi pemasaran untuk meningkatkan pendapatan Kios Polos - Hadisantono; Evangeli, Monica Valentina; Hanandoko, Theodorus B.; Dewa, Parama Kartika (Universitas Atma Jaya Yogyakarta, 2024)
Kios Polos is an MSME in the Special Region of Yogyakarta that specialises in slow fashion. The clothing offered focuses on the design of unisex clothing models. The target customers are divided into two categories, namely adults and teenagers. Since the beginning of the Kios Polos business, from May 2023 to April 2024, the business owner concluded that product sales at Kios Polos were dominated by adult customers. The state of the business also experienced stagnant sales at around Rp4,000,000.00. Therefore, the target revenue increase is 12.11% per week, when compared to the average revenue per week from February 2024 to April 2024. Based on these problems, this research was resolved by designing a marketing strategy. Some of the selected solution steps include collaboration with external parties, efficient use of budget, planning effective promotion strategies, bundling products, improving services, and customer reviews. The process of implementing the solution uses the Situational Analysis, Objectives, Strategy, Tactics, Actions, Control (SOSTAC) method. The research conducted succeeded in increasing engagement on Tiktok social media, but an increase in revenue of 12.11% per week, when compared to the average revenue per week from February 2024 to April 2024 from the implementation results, has not been achieved. This is due to the use of a soft selling strategy, so that time is not enough.